2007
DOI: 10.1007/s10267-006-0329-1
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic and epiphytic phyllosphere fungi of red-osier dogwood (Cornus stolonifera) in British Columbia

Abstract: Endophytic and epiphytic phyllosphere fungi associated with red-osier dogwood (Cornus stolonifera), a deciduous shrub, were examined in coastal British Columbia, Canada. Current-year shoots were divided into four types based on the absence or presence of infl orescence and secondary elongated shoots at the apex of primary shoots. Leaves on these shoots were then classifi ed into six categories so as to examine the effect of fl owering, secondary shoot elongation, and shoot order within currentyear shoots on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
5
10
1
Order By: Relevance
“…Very few studies have compared endophytic and epiphytic fungi, especially in fresh fruits. Comparison of epiphytic and endophytic fungal communities on single leaves of deciduous shrubs (Osono, 2007) or of woody plants (Osono, 2008), supporting our findings. The higher number of epiphytes recovered suggests that the external environment suits the fungal population colonizing the surface of olive fruit, despite the harsh environmental conditions that typify this habitat (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Very few studies have compared endophytic and epiphytic fungi, especially in fresh fruits. Comparison of epiphytic and endophytic fungal communities on single leaves of deciduous shrubs (Osono, 2007) or of woody plants (Osono, 2008), supporting our findings. The higher number of epiphytes recovered suggests that the external environment suits the fungal population colonizing the surface of olive fruit, despite the harsh environmental conditions that typify this habitat (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…phenolic compounds) and/or host plant defense reactions (Rastogi et al, 2013). Similarly, the composition of fungal communities inhabiting the surface of olives was completed different from that found in internal olive tissues, a pattern which has also been noted in previous studies performed in leaves (Osono, 2007(Osono, , 2008. Only Cladosporium cladosporioides, out of the 27 fungal OTUs recovered in this study, was common to both fungal floras.…”
Section: Discussionsupporting
confidence: 78%
“…These results agree with other reports on endophytes where it is reported that many fungal species can be isolated from a given host, but only very few are found frequently (Petrini et al 1992). In the literature, the genera Alternaria, Colletotrichum, Phomopsis and Guignardia are reported to be found most often as endophytes in various host plant tissues (Larran et al 2001;Larran et al 2002;Hata et al 2002;Santamaría and Bayman 2005;Chareprasert et al 2006;Osono 2007;Verma et al 2007;Lin et al 2007). …”
Section: Resultsmentioning
confidence: 96%
“…Five leaf quarters from each plant were plated onto Potato Dextrose Agar (PDA, Carolina Biological, Burlington, NC) in 2012 and four leaf quarters were plated onto PDA in 2013. Petioles were removed before plating and in order to target epiphytic fungi on the leaf lamina, leaves were not surface sterilised (Osono 2007). The PDA plates were incubated at 22 ° C and fungal colonies were aseptically transferred to separate PDA plates to obtain pure fungal isolates.…”
Section: Methodsmentioning
confidence: 99%